Kinetics of element release by weathering in soils of southern Ecuador: A comparison among different climatic and land-use regimes - Daniel Schöndorf; Nuria Basdediós; Andre Velescu; Tobias Fabian; Carlos Iván Espinosa; Wolfgang Wilcke (Geoderma)
To predict future changes in nutrient availability in the young soils of the tropical Andes, it is important to study the response of weathering rates to climate and land-use change. This is particularly true in highly biodiverse tropical forests, where increasing nutrient availability can threaten their biodiversity. Hence, our objectives were to compare the kinetics of element release by weathering along an elevation gradient and between forest and pasture in a tropical montane forest region in south Ecuador. We collected soil samples from three plots in both natural forest and pasture, at elevations of 1000, 2000, and 3000 m above sea level (a.s.l., i.e., 18 in total). The sites at 2000 and 3000 m a.s.l. had similar parent material and allowed for evaluating the climatic effect. To assess element mobilization from the soil, we conducted a weathering experiment at a constant pH value (pHstat). During the experiment, ions were released from the soil into solution at pH 3 and removed from the solution using an ion-exchange resin. We described the release of base cations (Ca, Mg, K), Mn, Al, and Fe with a two-step first-order reaction, distinguishing a fast-reacting pool (FP) and a slow-reacting pool (SP), with their associated rate constants. The FP of Ca, Mg, K, and Mn closely correlated with and corresponded in size to the concentrations of the exchangeable cations of these elements (r = 0.78 – 0.96). The FP of Ca, Mg, K, and Mn was significantly larger in the soils under pasture than under forest vegetation, likely because of the input of alkaline ashes during slash-and-burn practices. The sizes of the FP and the SP of all studied elements under both land covers/uses were not significantly different between the sites at 2000 and 3000 m a.s.l., possibly because the opposing effects of increasing precipitation and decreasing temperature canceled each other out. Metal release kinetics differed markedly among sites with different parent materials, indicating that weathering is strongly influenced by the chemical composition of the parent rocks. Our study illustrates that element release by weathering in the soils of south Ecuador is strongly influenced by differences in land cover/use and chemical composition of parent rocks.